BREAST CANCER SUBTYPES IN PAKISTANI POPULATION: DATA FROM A SINGLE CENTER - BANO , K; RIAZ , S; ZAFAR , A; SHEIKH , F; RASHID , AA; ISMAIL , Z (Biological and Clinical Sciences Research Journal, 2023)
Breast cancer is a complex disease that includes different types of tumors. These tumors can vary in their characteristics, such as the levels of estrogen, progesterone, and HER2/neu receptors. These differences can impact how the tumors respond to treatment, progress, and change over time. The study conducted at the Department of Oncology, Jinnah Hospital, Lahore, from May to November 2019, was a cross-sectional study that involved 90 female patients with breast cancer aged 25 to 75. The researchers analyzed the tumor samples using immunohistochemistry to evaluate ER, PR, and HER2neu levels. FISH was used to evaluate models that had equivocal HER2 by IHC. The participants in this study were 25 to 75 years old, with an average age of 47.10 ± 11.55 years. The average duration of the disease before presenting to the hospital was 6.71 ± 2.63 months. The study found that 74.44% of the female patients had tumors that were ER-positive, 56.67% had tumors that were PR-positive, and 20.0% had tumors that were HER2neu-positive. In conclusion, this study showed that the frequency of positive expression of estrogen, progesterone, and HER2neu in breast cancer patients in this population was consistent with international rates. However, more extensive studies are necessary to determine the exact prevalence of these tumors.